8.2.1 To V or not to V – that MUST be the Question Knowing When to Apply the Right Approach. Issue 1 (July 2014) - Cowper, Doug; Elphick, Jon; Kemp, Duncan; Evans, Rhianne
Abstract The last 20 years have shown a dramatic expansion in Systems Engineering theory, knowledge, knowhow and practical application. Despite this increase, there is evidence within organisations that there has been a growing gap between the SE required and the SE delivered. The authors of this paper describe the results of a study into the reasons for this gap, based on an on‐line survey which received 85 valid responses. The authors conclude that: Project professionals are using approaches that are not appropriate to the problems being tackled; Behaviour is being driven by narrow views of what organisations believe is right, rather than the broader range of practice that they allow; Project professionals adopt preferred approaches which they apply across more than one type of problem. The authors demonstrate that there is truth in the assertion that Systems Engineers apply the same approach, irrespective of the situation. Whilst standard Systems Engineering approaches, for example the V lifecycle, are the right approach in the complicated space, it is less appropriate in simple, complex or chaotic spaces. All too often, projects start with the assumption that we should use standard Systems Engineering approaches that we have used before, rather than ask: 'To V or not to V?'